Effects of controversial contexts on opinion changes through discussion and evaluation of decisions: A group decision experiment regarding the issue of removed soil in Fukushima - Yume Souma; Yukihide Shibata; Mie Tsujimoto; Qinglin Cui; Takashi Nakazawa; Tomoyuki Tatsumi; Yoshiko Arima; Susumu Ohnuma (PLoS ONE, 2026)
Designing settings that enable structured deliberation is crucial, particularly for contentious public issues, as debates can sometimes shift opinions toward extremes, create social division, and make it difficult to evaluate decisions positively. Constructive controversy has been proposed to avoid such breakdowns. However, only a few empirical studies have been conducted in the context of contentious public issues. This study aims to examine how competitive and cooperative controversies influence opinion change and decision evaluation in the context of public decision-making by conducting a group decision experiment. The discussion topic was the final disposal of the removed soil outside Fukushima Prefecture, which was caused by a nuclear power plant accident. The removed soil is currently stored in facilities in the towns of Okuma and Futaba, Fukushima Prefecture. By law, the government must complete the final disposal of the removed soil outside Fukushima Prefecture by 2045. The participants were 128 Japanese university students. This study manipulated controversial contexts as independent variables. One was a competitive context condition, whereby participants refuted opposing opinions, and the other was a cooperative context condition, whereby participants contemplated both pros and cons thoroughly. Each group consisted of four participants, and there were 32 groups in total (16 per condition). Participants in both conditions discussed and decided whether to approve the final disposal of the removed soil outside Fukushima Prefecture. The results indicated no significant differences in opinion changes between the conditions. However, participants in the cooperative condition evaluated their decisions more positively than those in the competitive condition did. Notably, under competitive conditions, participants whose pre-discussion opinions were not reflected in the groups’ decisions tended to rate outcomes less favorably. These findings contribute to a deliberative design and lead to more structured discussions on public issues.